Exploring Factors Behind Low Bed Occupation Rate of Hospital: A Case Study - Umi kulsum; Gunawan; Devita Rahmani Ratri (Universitas Muhammadiyah Yogyakarta, 2023)
Bed Occupancy Rate (BOR) Psychiatric Hospital of DR.Radjiman W regency had a low percentage. In April 2022, it was 59,80%, May at 50,55%, and June at 48,84%. It may be due to the governor’s and BPJS regulations, the development of psychiatric in other health services, the limited facilities and infrastructure for non-psychiatric patients, and the lack of information about non-psychiatric services. This study analyzed the low percentage of BOR (Bed Occupancy Rate). The sample was four respondents: the head of the inpatient, the head of the outpatient, the head of the emergency room, and the public relation. The main priority is to solve this research problem using the 5 WHYs and find an alternative solution by discussion method with all respondents. The result showed the main factor causing the low percentage of BOR in RSJRW was the lack of facilities and infrastructure. It was suggested that RSJRW should be aware of cleaning up and provide fewer facilities and infrastructure.